Development of Metamaterials Based Electromagnetic Structures - Sharma, Atipriya (My University, 2021)
Metamaterials (MM) are artificial or synthetic structures which possess unique properties such as negative permittivity (ε), permeability (µ), and refractive index, etc. The unique and useful properties of MM are offered by the shape, size, and arrangements of the unit cell, rather than the composition of the material. Conventional absorbers having larger thickness resulting in bulky, expensive, and narrow bandwidth that are replaced by the MM based absorbers (MMA). By considering the disadvantage of the conventional absorbers, in this thesis, MM based absorbers and low radar cross-section (RCS) antennas have been investigated. First of all, in this thesis, two distinct MM-based absorbers are designed, simulated, and measured in the range of 2 to 18 GHz. The first MMA is a hybrid structure that comprises of a cross-loaded split ring. The other proposed structure comprises eight sectors loaded circle inside the square. The first MMA show the reflection coefficient (RC) is less than -10 dB from 8.5 to 16 GHz for the hybrid structure, which covers 7.5 GHz bandwidth. The other proposed structure exhibits the four RC resonant peaks of -25.9 dB, -18.9 dB, -16.1 dB, and -21.3 dB are noticed at 4.4 GHz, 6.0 GHz, 14.1 GHz, and 16.0 GHz, respectively. To evaluate the optimized values of the distinct dimensions the parametric studies have been performed on both the structures. Further, an effort has been made to determine the angular stability and polarization sensitivity of the proposed structures. The frequency-dependent EM properties of both structures are also demonstrated in this chapter. Further, the surface current, electric (E) field, and magnetic (H) field distributions are also found. Finally, the proposed prototypes have been fabricated to evaluate the measured results. The free-space microwave measurement setup is used for the performance evaluation of the fabricated prototypes. Next, an efficient tunable absorber based on an active frequency selective surfaces (AFSS) utilizing p-i-n diode is presented. Initially, the AFSS has been designed, simulated, and analyzed using the CST studio. Further, the design of the active absorber which is based on AFSS is also presented. Another study is executed on AFSS loaded absorber with diode and without diode, to know its effect on the absorption characteristics. A single-layered, tunable, wideband AFSS based absorber is presented, which demonstrates the tunability in the range of 9.2 GHz to 11.2 GHz. To obtain the tunability AFSS loaded absorber with different values of resistance has been evaluated. The normalized impedance, surface current, E field, and H field distributions are also presented. Finally, the proposed prototype has been fabricated to evaluate the measured result. Further, two low RCS antennas are developed, which are based on MM techniques. The first one is MM inspired antenna and the second one is flexible MM-based superstrate coupled MPA, which enhances the gain along with RCS reduction (RCSR) of the MPA. The proposed MM impinged MPA it can be concluded that the structure provides RCSR, without affecting the other radiation properties and volume of the antenna. The reflection coefficient bandwidth of the second proposed MPA is the 800MHz, though the RCS bandwidth of the primary antenna is 1.7 GHz and the RCS bandwidth of the proposed antenna is 8.1 GHz. The increment in gain is observed in the proposed antenna. It can be observed that the maximum gain attained by the primary antenna is equal to 6.6 dB, whereas the maximum gain of the proposed antenna is equal to 7.2 dB. To evaluate the optimized values of the distinct dimensions, parametric studies have been performed on both the structures. Finally, the proposed prototypes have been fabricated to evaluate the measured results. The performance evaluation of the fabricated antennas has been carried out using a microwave measurement setup. A good agreement has been observed between the simulated and measured results of all the prototypes.
Keywords: Metamaterial; Antenna; RCS; FSS; Absorber